A land-use spatial optimization model based on genetic optimization and game theory. (January 2015) - Liu, Yaolin; Tang, Wei; He, Jianhua; Liu, Yanfang; Ai, Tinghua; Liu, Dianfeng
Highlights: A land-use spatial optimization model that emphasizes coordinating local land-use competitions is constructed. An improved genetic algorithm is utilized to optimize the spatial layout of each land-use type. Interest factors are introduced into the land-use coordination through multi-stakeholder games. The model supports decision-making for regional land-use planning. Abstract: Land-use patterns can be considered as a consequence of competitions between different land-use types. How to coordinate the competitions is the key to land-use spatial optimization. In order to improve the ability of existing land-use spatial optimization models for addressing local land-use competitions (the competitions on land units), a loosely coupled model based on a genetic algorithm (GA) and game theory is constructed. The GA is repeatedly executed to separately optimize the spatial layout of each land-use type. The land-use status quo is overlaid with the optimization results to find local land-use competitions. The concept of land-use competition zones is introduced in this study. Using the competition zones as the basic units, the model utilizes multi-stakeholder games and the knowledge of land-use planning to coordinate the local land-use competitions. The final solution is obtained after the land-use coordination. Gaoqiao Town, Zhejiang Province is selected as the study area to verify the validity of the model. The experimental results confirm that the model is feasible to undertake land-use spatial optimization and to coordinate the competitions between different land-use types.